Comparative Rates of Serious Infections Among Patients With Systemic Lupus Erythematosus Receiving Immunosuppressive Medications. Issue 2 (February 2017) - Feldman, Candace H.; Marty, Francisco M.; Winkelmayer, Wolfgang C.; Guan, Hongshu; Franklin, Jessica M.; Solomon, Daniel H.; Costenbader, Karen H.; Kim, Seoyoung C.
Abstract : Objective: While infection burden is high among patients with systemic lupus erythematosus (SLE), there is uncertainty about whether infection rates differ by immunosuppressive drug regimens. We undertook this study to compare infection rates among SLE patients newly initiating immunosuppressive therapy with mycophenolate mofetil (MMF), azathioprine (AZA), or cyclophosphamide (CYC). Methods: Within the Medicaid Analytic eXtract database (2000–2010; 29 most populated US states), we identified adults with SLE starting MMF, AZA, or CYC treatment. We estimated propensity scores for receipt of MMF versus AZA and MMF versus CYC based on sociodemographic, comorbidity, and medication use information. After 1:1 propensity score matching, we estimated incidence rates of serious infections up to 6 and 12 months after drug initiation and used Cox regression to estimate hazard ratios (HRs) of first infection and death, with 95% confidence intervals (95% CIs). We performed primary intent‐to‐treat (ITT) and secondary as‐treated analyses. Results: We studied 1, 350 propensity score–matched pairs of MMF and AZA initiators and 674 propensity score–matched pairs of MMF and CYC initiators. In 6‐month ITT analyses, the incidence rate per 100 person‐years for first serious hospitalized infection was 14.6 in MMF users and 15.2 in AZA users (HR of MMF versus AZA 0.99 [95% CI 0.74–1.32]). Comparing MMF to CYC, the incidence rate per 100 person‐years for first serious infection was 24.1 in MMF users and 24.6 in CYC users (HR 0.95 [95% CI 0.69–1.32]). There were no differences in mortality in either comparison. As‐treated analyses yielded similar results. Conclusion: In a nationwide longitudinal study of Medicaid SLE patients at high risk of infection, rates of serious infection and mortality did not differ among new users of MMF, AZA, or CYC.